Implementation of attendance machine for entrance access system based on barcode scanning - Bakti Viyata Sundawa; Faisal Lubis; Cholish Cholish (Jurnal Mandiri IT, 2023)
Attendance in Universitas Muhammadiyah Sumatera Utara (UMSU) uses the manual attendance method. So it is less effective to implement, because manual attendance is not environmentally friendly and in the process fraud can still occur. In addition, the health protocols that we should have implemented both on campus and in classrooms must still exist considering this is a post-pandemic. Based on these problems, the purpose of this research is to make a prototype of the entrance and attendance access system which is carried out by utilizing the features on the NodeMCU ESP32. The design step is divided into 2, namely hardware and software design. The manufacturing process for the door access system is carried out by utilizing the Gy906 temperature sensor as a body temperature detector, a relay to turn on the pump, an IR proximity sensor to detect people who are going out, and a servo motor as an open- or closed-door driver. Next, the process of making attendances is carried out using a barcode on the KTM (Student Identity Card) which is connected to the application that has been made so that the output for the presence can be seen on a google spreadsheet. This tool can make it easier to make attendance and access entrances and exits without touching the door.